Multi-omics insights into Chinese herbal medicine additives for mutton flavor enhancement: epigenetic and microbial mechanisms - Quan, Kai; Shi, Huibin; Han, Haoyuan; Liu, Kun; Cui, Qiufang; Wang, Huihua; Jin, Meilin; Sun, Wei; Wei, Caihong; Jiang, Yibao; Li, Jun (Frontiers in Veterinary Science, 2025)
Chinese herbal medicine additives (CHMAs) have become increasingly popular as sustainable alternatives to synthetic compounds for improving the quality of mutton. However, the precise molecular mechanisms underlying their effects are not well understood. By integrating transcriptomic profiling, metabolomic pathways, and microbial community dynamics, this review deciphers the synergistic mechanisms of CHMAs in enhancing mutton flavor, supported by empirical evidence from 2014 to 2024. Our key findings highlight three synergistic pathways: (1) Epigenetic suppression of FASN and CYP2B6 via DNA methylation leads to a reduction of odor precursors like 4-methyloctanoic acid by 30–50% (p < 0.01); (2) Mulberry leaf flavonoids activate β-oxidation, increasing linoleic acid content by 25%, thereby improving tenderness and juiciness; (3) Licorice polysaccharides, in collaboration with Ruminococcus-enriched microbiota, enhance flavor volatiles such as 2-acetylthiazoline. It is important to consider dose-dependent thresholds, as thyme phenolic extract at 0.05% maximizes aroma intensity (p < 0.05), while exceeding 1.5% licorice glycyrrhizin intensifies gaminess. Species-specific responses highlight variations in rumen microbial activity, with Tan sheep showing a 30% increase in catalase activity compared to goats. Validated by the Luoyang Longxupo industrial model, which achieved a 30% reduction in odor and received Green Food Certification, this study proposes a unique gene-metabolite-microbe interaction network that emphasizes the significance of epigenetic-microbial crosstalk. We also discuss challenges related to herbal synergies, sensory standardization, and offer solutions through AI-driven optimization, with an AUC of 0.89, as well as the potential application of cultured meat, such as Salvia miltiorrhiza reducing lipid oxidation by 40% in vitro. These findings connect traditional herbal knowledge with precision agriculture, providing practical strategies for environmentally friendly mutton production that meets the global demand for safe, high-quality protein.